2013
DOI: 10.3329/jme.v42i1.15941
|View full text |Cite
|
Sign up to set email alerts
|

Emission Characteristics of Jatropha-Ethanol and Jatropha- Dimethyl Ether Fuel Blends on a Di Diesel Engine

Abstract: Abstract:In this study, Biodiesel -Dimethyl Ether (BDE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The primary focus has been on the use of biodiesel in diesel engines [1][2][3][8][9][10][11]. The compatible physiochemical properties of biodiesel to diesel fuel have allowed up to 20% blending of biodiesel with petroleum diesel for the application in diesel engines without any modification [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The primary focus has been on the use of biodiesel in diesel engines [1][2][3][8][9][10][11]. The compatible physiochemical properties of biodiesel to diesel fuel have allowed up to 20% blending of biodiesel with petroleum diesel for the application in diesel engines without any modification [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, oxygenate additives were used by different researchers to improve the performance and emissions of diesel engines. Loganathan et al [18] used dimethyl ether (DME) as an additive to enhance combustion characteristics. They experimentally determined the effect of dimethyl ether (DME) with Jatropha biodiesel in a diesel engine.…”
Section: Introductionmentioning
confidence: 99%
“…al. has conducted experiment on single cylinder direct diesel engine by reduced compression ratios from 17:1 to 16.5:1 with different blends of diesel with Jatropha and analysed emission, combustion and performance characteristics, it is found that reducing compression ratios and usage of biodiesel produces almost similar amount of NOx but with lesser smoke [1]. M. Loganathan et.…”
Section: Biodiesel Performance Combustion and Emission Charactermentioning
confidence: 99%